Call Center operation design, operation, and maintenance - Sharp, Duane E. (Amsterdam ; Boston : Digital Press, 2003)
Complete coverage of the critical issues to set up, manage and efficiently maintain a call center.
Introduction to call centers -- Call center technology -- Organizing and managing the call center -- Selecting and training call center staff -- Call center case studies -- Building customer relationships with call centers.
Includes bibliographical references (p. 283-285) and index.
Keywords: Call centers -- Management; Electronic books